High-temperature denitration catalyst and preparation method thereof
Nanoflake-like TiO2-Al2O3 oxide was prepared by sol-gel method and impregnated with vanadium and molybdenum sources to prepare V2O5-MoO3/TiO2-Al2O3 high-temperature denitrification catalyst, which solved the poor denitrification activity and resistance of existing catalysts under high temperature conditions. The problem of poor sulfur performance has achieved efficient nitrogen oxide emission reduction.
Patent Information
- Application Number
- CN202411496192.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-18
AI Technical Summary
Existing SCR catalysts have poor denitrification activity and poor sulfur resistance under high temperature conditions, making it difficult to effectively reduce nitrogen oxide emissions.
Nanoflake-like TiO2-Al2O3 oxide was prepared by sol-gel method, and the relative proportion of five-coordinated aluminum was regulated by alcohol polymers. Then it was impregnated with vanadium and molybdenum sources to prepare V2O5-MoO3/TiO2-Al2O3. High temperature denitrification catalyst.
Under high temperature and high sulfur flue gas conditions, the catalyst exhibits excellent denitrification activity and sulfur resistance, with denitrification performance up to 85%-95%, and sulfur resistance up to 60.8%-75.3%, significantly improving the performance of existing catalysts .
Smart Images

Figure CN119455931A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of flue gas denitration catalysts, and in particular to a high-temperature denitration catalyst and a preparation method thereof. Background Art
[0002] With the rapid development of the economy, the traditional extensive development model with high consumption, high emissions, difficult recycling and low efficiency can no longer meet the current needs of sustainable development. Nitrogen oxides (NOx) are a source of air pollution that can cause serious damage to the environment, such as stratospheric ozone depletion, acid deposition, and photochemical smog, and have great harm to the human ecological environment. As the main source of nitrogen oxide emissions in my country, it is urgent to reduce nitrogen oxide emissions from coal-fired power plants.
[0003] Ammonia selective catalytic reduction (SCR) has been proven to be the most effective NOx emission reduction control technology, the core of which is the SCR denitrification catalyst.
[0004] The current commercial SCR catalyst has an operating temperature window of about 180-450°C and is now widely used in coal-fired power plants, steel, coking, glass and other industries. However, due to the complexity of industrial flue gas conditions and the limitations of SCR reactor layout, when the flue gas temperature exceeds 450°C, the denitrification efficiency of the catalyst will drop significantly, the N2O byproduct will rise sharply, and the oxidation process of SO2 will be accelerated, causing the catalyst to deactivate rapidly. Therefore, it is very necessary to develop a catalyst with high denitrification activity suitable for high-temperature and high-sulfur flue gas conditions.
[0005] Chinese invention patent CN113083286A discloses a method for preparing an ultra-high temperature denitration catalyst, which mainly first obtains a catalyst carrier with a pyrochlore structure and strong surface acidity through a sol-gel method, and then loads the catalyst active components to obtain an ultra-high temperature catalyst. The pyrochlore structure gives the catalyst excellent thermal stability, overcoming the problem of high temperature specific thermal shrinkage of the catalyst. At the same time, the strong surface acidity of the pyrochlore-type lanthanum-zirconium composite oxide reduces the ammonia oxidation property of the catalyst, which makes the catalyst also have excellent denitration performance under ultra-high temperature conditions. However, the ultra-high temperature catalyst prepared by the sol-gel method has a pyrochlore structure, which is relatively dense and has a very low specific surface area (<32m 2 / g), which is not conducive to the uniform dispersion of active components, and the active sites are not fully utilized, which has certain limitations in practical applications.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The purpose of the present invention is to provide a high-temperature denitration catalyst and a preparation method thereof. The high-temperature denitration catalyst prepared by the present invention has excellent denitration activity and sulfur resistance under high-temperature and high-sulfur flue gas conditions, which effectively solves the problem that the existing denitration catalyst has poor denitration activity and poor sulfur resistance under high-temperature conditions.
[0008] In a first aspect, the present invention provides a method for preparing a high-temperature denitration catalyst, comprising the following steps:
[0009] S1, adding a titanium source, an aluminum source and an alcohol polymer to anhydrous ethanol, heating and stirring to obtain a mixed solution;
[0010] S2, adding a mixed solution of anhydrous ethanol and distilled water dropwise into the mixed solution of step S1 for hydrolysis to obtain an initial gel, and the initial gel is dried and calcined to obtain a nano-sheet TiO2-Al2O3 oxide;
[0011] S3. The nano-sheet TiO2-Al2O3 oxide is impregnated with a vanadium source and a molybdenum source, and then dried and calcined to obtain a V2O5-MoO3 / TiO2-Al2O3 high-temperature denitrification catalyst.
[0012] In the preparation method of the high-temperature denitration catalyst of the present invention, TiO2-Al2O3 oxide is first prepared by a sol-gel method, and an alcohol polymer is added as a surfactant or template to control the process of hydrolysis and polycondensation reaction, thereby preparing a nano-sheet TiO2-Al2O3 oxide. Studies have shown that the alcohol polymer introduced by the present invention can increase the relative proportion of penta-coordinated aluminum in the nano-sheet TiO2-Al2O3 oxide, and the increase in the proportion of penta-coordinated aluminum can effectively promote the uniform dispersion of V and Mo active species on the surface of the nano-sheet TiO2-Al2O3 oxide, and expose more active sites. Further, the nano-sheet TiO2-Al2O3 oxide is impregnated in a vanadium source and a molybdenum source, and dried and calcined to obtain a V2O5-MoO3 / TiO2-Al2O3 high-temperature denitration catalyst. The increase in active sites further enhances the interaction between the active species and the carrier, thereby more effectively preventing the sintering and agglomeration of the active components at high temperatures. Therefore, the high-temperature denitration catalyst of the present invention has excellent denitration activity and sulfur resistance under high-temperature and high-sulfur flue gas conditions, effectively solving the problem of poor denitration activity and sulfur resistance of existing denitration catalysts under high-temperature conditions.
[0013] As a preferred embodiment of the present technical solution, in step S1, the alcohol polymer used in the present invention includes any one or more of polypropylene alcohol, polyvinyl alcohol and poly 1,4-butylene glycol. The above substances can form a stable complex with aluminum ions, thereby changing the charge and polarity of the surface of the reactants, so that the TiO2-Al2O3 oxide presents a nanosheet structure. At the same time, the complex formed by the above alcohol polymer and aluminum ions can also control the hydrolysis rate of aluminum ions, thereby promoting the formation of a pentacoordinate aluminum structure.
[0014] As a preferred embodiment of the present technical solution, in step S1, the titanium source used in the present invention includes any one of titanium isopropoxide, tetrabutyl titanate and isopropyl titanate; the aluminum source includes any one of aluminum isopropoxide, aluminum sec-butoxide and aluminum ethoxide, wherein the mass ratio of the oxide corresponding to the titanium source and the aluminum source is 1:(0.1-0.9); and the mass ratio of the oxide corresponding to the titanium source to the alcohol polymer is 1:(0.3-10).
[0015] As a preferred embodiment of the present technical solution, in step S1, when the present invention heats and stirs the titanium source, the aluminum source and the alcohol polymer, the temperature needs to be controlled to be 30-60°C and the time is 0.5-2h. This is because in the sol-gel reaction process, the concentration of the reactants, the reaction temperature and the reaction time have an important influence on the formation of the complex and the formation of pentacoordinated aluminum. Therefore, by optimizing the reaction conditions, the formation of pentacoordinated aluminum can be promoted and its relative proportion can be increased.
[0016] In step S1 of the present invention, the titanium source is preferably titanium isopropoxide, the aluminum source is preferably aluminum ethoxide, the alcohol polymer is preferably polypropylene alcohol, the mass ratio of the oxides corresponding to the titanium source and the aluminum source is preferably 1:0.5, and the mass ratio of the oxide corresponding to the titanium source to the alcohol polymer is preferably 1:4.5.
[0017] As a preferred embodiment of the present technical solution, in step S2, after preheating the mixed solution of anhydrous ethanol and distilled water, it is added dropwise to the mixed solution of step S1 for hydrolysis. During the hydrolysis, the temperature is controlled to be 30-60°C and the time is 1-3h. The morphology of the product is further controlled by controlling the progress of the hydrolysis and polycondensation reaction, and the formation of penta-coordinated aluminum is promoted. Finally, the product is dried at 80-130°C for 12-48h, and then calcined at 450-550°C for 6-12h. The structure and performance of the product are further improved by post-processing to remove excess solvents and impurities, promote the crystallization and phase change of the product, and thus improve the stability and relative proportion of penta-coordinated aluminum.
[0018] As a preferred embodiment of the present technical solution, in step S3, the present invention further impregnates the nano-sheet TiO2-Al2O3 composite oxide into a vanadium source and a molybdenum source, and after drying and calcination, a V2O5-MoO3 / TiO2-Al2O3 high-temperature denitrification catalyst can be obtained.
[0019] Specifically, the vanadium source used in the present invention includes any one or more of ammonium metavanadate, ammonium vanadate and vanadyl oxalate; the molybdenum source includes any one or more of ammonium heptamolybdate, molybdenum nitrate, molybdenum sulfate and molybdenum chloride.
[0020] As a preferred embodiment of the present technical solution, in step S3, during drying, the temperature is controlled to be 80-120°C and the time is 1-4h; during roasting, the temperature is controlled to be 450-500°C and the roasting time is 4-10h.
[0021] As a preferred embodiment of the present technical solution, in step S3, in the high-temperature denitration catalyst prepared by the present invention, the mass fraction of V2O5 is 0.8%-2.0%, and the mass fraction of MoO3 is 1%-4.5%.
[0022] In the second aspect, the present invention also discloses a high-temperature denitration catalyst prepared by the above-mentioned preparation method, which should also fall within the protection scope of the present invention.
[0023] The preparation method of the high-temperature denitration catalyst of the present invention has at least the following beneficial effects:
[0024] 1. The present invention adopts a sol-gel method to prepare nano-flaky TiO2-Al2O3 oxides. The relative proportion of penta-coordinated aluminum in the nano-flaky TiO2-Al2O3 oxides can be increased by adding alcohol polymers. The increase in the proportion of penta-coordinated aluminum can effectively promote the uniform dispersion of V and Mo active species on the surface of the nano-flaky TiO2-Al2O3 oxides and expose more active sites. At the same time, the interaction between the active species and the carrier can be further enhanced, thereby more effectively preventing the sintering and agglomeration of the active components at high temperatures;
[0025] 2. The high-temperature denitration catalyst of the present invention has high denitration activity and sulfur resistance under high-temperature and high-sulfur flue gas conditions. At 350-550°C, the denitration performance can reach 85%-95%, and the sulfur resistance can reach 60.8%-75.3%, which effectively solves the problem of poor denitration activity and poor sulfur resistance of existing denitration catalysts under high-temperature and high-sulfur flue gas conditions;
[0026] 3. The high-temperature denitration catalyst preparation method of the present invention has relatively mild reaction conditions, simple process, low production cost, can be industrialized and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0028] Figure 1 This is a SEM photo of the V2O5-MoO3 / TiO2-Al2O3 high temperature denitration catalyst obtained in Example 1 of the present invention;
[0029] Figure 2 SEM photo of the denitration catalyst obtained in Comparative Example 1 of the present invention;
[0030] Figure 3 SEM photo of the denitration catalyst obtained in Comparative Example 2 of the present invention;
[0031] Figure 4 SEM photo of the denitration catalyst obtained in Comparative Example 3 of the present invention;
[0032] Figure 5 SEM photograph of the denitration catalyst obtained in Comparative Example 4 of the present invention. DETAILED DESCRIPTION
[0033] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0034] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form also includes the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this description, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0035] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Example 1
[0037] S11, dissolving 4.27 g of aluminum isopropoxide, 1.53 g of titanium isopropoxide and 1.5 g of polyvinyl alcohol in 40 mL of anhydrous ethanol, and heating in a water bath at 35° C. for 1 h to obtain a mixed solution;
[0038] S12, placing a mixed solution of 9 mL of distilled water and 90 mL of anhydrous ethanol in a 35° C. water bath for 15 min, then slowly adding the solution to the mixed solution prepared in step S11, and continuing stirring for 1 h to form an initial gel; placing the obtained initial gel in a 120° C. drying oven for 48 h, placing the obtained dry gel in a muffle furnace, and calcining it at 500° C. for 5 h in an air atmosphere to obtain nano-sheet TiO2-Al2O3 oxide;
[0039] S13. Ammonium metavanadate and ammonium heptamolybdate are loaded on a nano-sheet TiO2-Al2O3 oxide carrier by an equal volume impregnation method. After being placed at room temperature for 24 hours, the carrier is placed in a drying oven at 100°C for 24 hours. Finally, the obtained sample is placed in a muffle furnace and calcined at 550°C for 4 hours to obtain a V2O5-MoO3 / TiO2-Al2O3 high-temperature denitrification catalyst, wherein the mass fraction of V2O5 is 1.0wt%, and the mass fraction of MoO3 is 2.2wt%.
[0040] Example 2
[0041] S21, dissolving 5.57 g of aluminum sec-butoxide, 2.32 g of isopropyl titanate and 1.7 g of polyvinyl alcohol in 50 mL of anhydrous ethanol, and heating in a water bath at 30° C. for 1 h to obtain a mixed solution;
[0042] S22, placing a mixed solution of 7 mL of distilled water and 90 mL of anhydrous ethanol in a 35° C. water bath for 15 min, then slowly adding the solution to the mixed solution prepared in step S21, and continuing stirring for 1 h to form an initial gel; placing the obtained initial gel in a 110° C. drying oven for 40 h; placing the obtained dry gel in a muffle furnace, and calcining it at 500° C. for 5 h in an air atmosphere to obtain nano-TiO2-Al2O3 oxide;
[0043] S23. Ammonium metavanadate and ammonium heptamolybdate are loaded on a nano-sheet TiO2-Al2O3 oxide carrier by an equal volume impregnation method. After being placed at room temperature for 24 hours, the carrier is placed in a drying oven at 90°C for 24 hours. The obtained sample is placed in a muffle furnace and calcined at 530°C for 4 hours to obtain a V2O5-MoO3 / TiO2-Al2O3 high-temperature denitrification catalyst, wherein the mass fraction of V2O5 is 1.3wt%, and the mass fraction of MoO3 is 2.7wt%.
[0044] Example 3
[0045] S31, dissolving 3.35 g of aluminum ethoxide, 0.95 g of isobutyl titanate and 5.4 g of polypropylene alcohol in 47 mL of anhydrous ethanol, and heating in a water bath at 40° C. for 1.5 h to obtain a mixed solution;
[0046] S32, placing a mixed solution of 12 mL of distilled water and 84 mL of anhydrous ethanol in a 35° C. water bath for 15 min, then slowly dropping it into the mixed solution prepared in step S31, and continuing stirring for 1 h to form an initial gel; placing the obtained initial gel in a 110° C. drying oven for 35 h; placing the obtained dry gel in a muffle furnace, and calcining it at 550° C. for 5 h in an air atmosphere to obtain nano-sheet TiO2-Al2O3 oxide;
[0047] S33. Ammonium metavanadate and ammonium heptamolybdate are loaded on a nano-sheet TiO2-Al2O3 oxide carrier by an equal volume impregnation method. After being placed at room temperature for 24 hours, the carrier is placed in a 90°C drying oven for 12 hours. The obtained sample is placed in a muffle furnace and calcined at 540°C for 4 hours to obtain a V2O5-MoO3 / TiO2-Al2O3 high-temperature denitrification catalyst, wherein the mass fraction of V2O5 is 0.8wt%, and the mass fraction of MoO3 is 3.5wt%.
[0048] Example 4
[0049] S41, dissolving 4.78 g of aluminum ethoxide, 0.65 g of isopropyl titanate and 2.2 g of polyvinyl alcohol in 37 mL of anhydrous ethanol, and heating in a water bath at 40° C. for 1.5 h to obtain a mixed solution;
[0050] S42, placing a mixed solution of 12 mL of distilled water and 84 mL of anhydrous ethanol in a 35° C. water bath for 15 min, then slowly adding the solution to the mixed solution prepared in step S41, and continuing stirring for 1 h to form an initial gel; placing the obtained initial gel in a 110° C. drying oven for 42 h; placing the obtained dry gel in a muffle furnace, and calcining it at 500° C. for 5 h in an air atmosphere to obtain nano-sheet TiO2-Al2O3 oxide;
[0051] S43. Ammonium metavanadate and ammonium heptamolybdate are loaded on a nano-sheet TiO2-Al2O3 oxide carrier by an equal volume impregnation method. After being placed at room temperature for 24 hours, the carrier is placed in a drying oven at 90°C for 12 hours. The obtained sample is placed in a muffle furnace and calcined at 550°C for 4 hours to obtain a V2O5-MoO3 / TiO2-Al2O3 high-temperature denitrification catalyst, wherein the mass fraction of V2O5 is 1.6wt%, and the mass fraction of MoO3 is 4.0wt%.
[0052] Example 5
[0053] S51, dissolving 4.78 g of aluminum sec-butoxide, 1.02 g of isopropyl titanate and 1.75 g of poly 1,4-butanediol in 50 mL of anhydrous ethanol, and heating in a water bath at 40° C. for 1 h to obtain a mixed solution;
[0054] S52, placing a mixed solution of 14 mL of distilled water and 70 mL of anhydrous ethanol in a 35° C. water bath for 15 min, then slowly adding the solution to the mixed solution prepared in step S51, and continuing stirring for 1 h to form an initial gel; placing the obtained initial gel in a 110° C. drying oven for 42 h; placing the obtained dry gel in a muffle furnace, and calcining it at 500° C. for 4 h in an air atmosphere to obtain nano-sheet TiO2-Al2O3 oxide;
[0055] S53. Ammonium metavanadate and ammonium heptamolybdate are loaded on a nano-sheet TiO2-Al2O3 oxide carrier by an equal volume impregnation method. After being placed at room temperature for 24 hours, the carrier is placed in a drying oven at 90°C for 12 hours. The obtained sample is placed in a muffle furnace and calcined at 550°C for 4 hours to obtain a V2O5-MoO3 / TiO2-Al2O3 high-temperature denitrification catalyst, wherein the mass fraction of V2O5 is 1.8wt%, and the mass fraction of MoO3 is 3.4wt%.
[0056] Example 6
[0057] S61, dissolving 4.78 g of aluminum sec-butoxide, 2.52 g of titanium isopropoxide and 1.32 g of poly 1,4-butanediol in 50 mL of anhydrous ethanol, and heating in a water bath at 40° C. for 1 h to obtain a mixed solution;
[0058] S62, placing a mixed solution of 18 mL of distilled water and 70 mL of anhydrous ethanol in a 35°C water bath for 15 min, then slowly adding it dropwise to the mixed solution prepared in step S61, and continuing stirring for 1 h to form an initial gel; placing the obtained initial gel in a 100°C drying oven for 48 h; placing the obtained dry gel in a muffle furnace, and calcining it at 480°C for 4 h in an air atmosphere to obtain nano-sheet TiO2-Al2O3 oxide;
[0059] S63. Ammonium metavanadate and ammonium heptamolybdate are loaded on a nano-sheet TiO2-Al2O3 oxide carrier by an equal volume impregnation method. After being placed at room temperature for 36 hours, the carrier is placed in a drying oven at 90°C for 12 hours. The obtained sample is placed in a muffle furnace and calcined at 530°C for 4 hours to obtain a V2O5-MoO3 / TiO2-Al2O3 high-temperature denitrification catalyst, wherein the mass fraction of V2O5 is 1.7wt%, and the mass fraction of MoO3 is 2.4wt%.
[0060] Example 7
[0061] S71, dissolving 4.78 g of aluminum sec-butoxide, 3.02 g of titanium isopropoxide and 1.32 g of polypropylene alcohol in 50 mL of anhydrous ethanol, and heating in a water bath at 40° C. for 1 h to obtain a mixed solution;
[0062] S72, placing a mixed solution of 17 mL of distilled water and 85 mL of anhydrous ethanol in a 35° C. water bath for 15 min, then slowly adding the solution to the mixed solution prepared in step S71, and continuing stirring for 1 h to form an initial gel; placing the obtained initial gel in a 100° C. drying oven for 48 h; placing the obtained dry gel in a muffle furnace, and calcining at 480° C. for 4 h in an air atmosphere to obtain nano-sheet TiO2-Al2O3 oxide;
[0063] S73. Use an equal volume impregnation method to load ammonium metavanadate and ammonium heptamolybdate on the nano-flake TiO2-Al2O3 oxide carrier in step S30, place it at room temperature for 36 hours, and then place it in a 90°C drying oven for treatment for 12 hours; place the obtained sample in a muffle furnace and roast it at 520°C for 6 hours to obtain a V2O5-MoO3 / TiO2-Al2O3 high-temperature denitrification catalyst, wherein the mass fraction of V2O5 is 1.5wt%, and the mass fraction of MoO3 is 2.7wt%.
[0064] Example 8
[0065] S81, dissolving 3.55 g of aluminum ethoxide, 0.95 g of titanium isopropoxide and 1.32 g of poly 1,4-butanediol in 50 mL of anhydrous ethanol, and heating in a water bath at 40° C. for 1 h to obtain a mixed solution;
[0066] S82, placing a mixed solution of 15 mL of distilled water and 80 mL of anhydrous ethanol in a 35° C. water bath for 15 min, then slowly adding the solution to the mixed solution prepared in step S81, and continuing stirring for 1 h to form an initial gel; placing the obtained initial gel in a 100° C. drying oven for 48 h; placing the obtained dry gel in a muffle furnace, and calcining it at 480° C. for 4 h in an air atmosphere to obtain nano-sheet TiO2-Al2O3 oxide;
[0067] S83. Vanadium oxalate and ammonium heptamolybdate are loaded on a nano-sheet TiO2-Al2O3 oxide carrier by an equal volume impregnation method. After being placed at room temperature for 36 hours, the carrier is placed in a drying oven at 100°C for 12 hours. The obtained sample is placed in a muffle furnace and calcined at 500°C for 6 hours to obtain a V2O5-MoO3 / TiO2-Al2O3 high-temperature denitrification catalyst, wherein the mass fraction of V2O5 is 2.0wt%, and the mass fraction of MoO3 is 2.0wt%.
[0068] Comparative Example 1
[0069] This control example is basically the same as Example 1, except that no alcohol polymer is added in this control example.
[0070] Comparative Example 2
[0071] Commercial TiO2 and Al2O3 mechanically mixed as carriers were used to load V2O5 and MoO3 to prepare denitrification catalysts.
[0072] Comparative Example 3
[0073] This control example is basically the same as Example 5, except that poly 1,4-butylene glycol is replaced by 1,4-butylene glycol.
[0074] Comparative Example 4
[0075] This control example is basically the same as Example 1, except that polyvinyl alcohol is replaced by vinyl alcohol.
[0076] Figure 1-5 The surface morphology of the denitration catalyst prepared by Example 1 of the present invention and Comparative Examples 1-4. As can be seen from the figure, compared with Comparative Examples 1-4, the morphology of the TiO2-Al2O3 composite in the high-temperature denitration catalyst of Example 1 of the present invention is formed by the accumulation of ultra-thin nanosheets, indicating that the addition of polyvinyl alcohol has a guiding effect on the growth of the TiO2-Al2O3 composite.
[0077] The present invention uses aluminum nuclear magnetic resonance to test the coordination environment and proportion of aluminum elements in the denitration catalyst carriers prepared in the above-mentioned Examples 1-8 and Comparative Examples 1-4. The test results are shown in Table 1.
[0078] Table 1
[0079]
[0080] The present invention further uses the above sample as a denitration catalyst to explore its catalytic performance, and the specific experimental method is as follows:
[0081] The reaction was carried out in a micro fixed bed reactor at atmospheric pressure, with a catalyst loading of 0.3 g. A mixture of NO, NH3, O2 and N2 was used to simulate industrial flue gas, where the volume fractions of NO, NH3 and O2 were 0.05%, 0.05% and 5% respectively, N2 was used as a balance gas, and the flow rate of the mixed gas was 1 L / min. A GA-21plus flue gas analyzer (Madur, Austria) was used to analyze the volume fractions of NO and NO2 in the mixed gas after the reaction, and the denitrification efficiency η was calculated according to the following formula: NO (%), the denitration efficiency of the catalyst at different temperatures was calculated by this formula, and the results are shown in Table 2.
[0082] η NO (%) = ([NO]in -[NO] out -[NO2] out ) / [NO] in ×100%
[0083] Table 2
[0084]
[0085] Combined with Table 1-2, it can be seen that the catalysts prepared in Comparative Examples 3-4 show poor denitration activity and N2 selectivity in the high temperature range (350-550°C), which may be because small molecule alcohols cannot change the coordination state of the carrier and can only play a dissolving role in the process of synthesizing the carrier. When the alcohol polymer is introduced into Example 1-8, the denitration activity of the catalyst is significantly improved, and the selectivity of N2 is also significantly improved. This may be because the presence of penta-coordinated aluminum in the nano-sheet TiO2-Al2O3 oxide prepared by the present invention helps to stabilize the active ingredients of the catalyst and prevent it from agglomerating or deactivating during the reaction, thereby improving the stability and service life of the catalyst; at the same time, the nano-sheet TiO2-Al2O3 oxide also has a special surface structure, which can enhance the adsorption capacity of the catalyst to the reactant, and this strong adsorption capacity helps the reactant to enrich and react on the catalyst surface, thereby improving the denitration efficiency; finally, the nano-sheet TiO2-Al2O3 oxide will also promote the generation of certain intermediates or stabilize certain key reaction intermediates, thereby optimizing the reaction path and improving the selectivity of the reaction.
[0086] The present invention also tests the sulfur resistance of the denitration catalyst, specifically at 400°C with a SO2 concentration of 2000 ppm. The sulfur resistance results of the catalysts obtained in Examples 1-8 and Comparative Examples 1-4 are shown in Table 3.
[0087] Table 3
[0088] project Sulfur resistance (400℃,%) Example 1 60.8 Example 2 63.4 Example 3 67.5 Example 4 75.3 Example 5 71.3 Example 6 65.4 Example 7 70.3 Example 8 74.6 Comparative Example 1 50.2 Comparative Example 2 37.0 Comparative Example 3 53.8 Comparative Example 4 50.5
[0089] It can be seen from Table 3 that the catalysts prepared by the comparative examples 1-4 of the present invention have poor anti-sulfur performance at 400°C. After the introduction of the alcohol polymer, the relative proportion of penta-coordinated aluminum in the carrier is significantly increased, and the increase of penta-coordinated aluminum promotes the dispersion of active species such as vanadium, thereby reducing the acidity of the catalyst. Therefore, the anti-sulfur performance of the catalyst is also significantly improved.
[0090] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a high-temperature denitration catalyst, characterized in that: The following steps are involved: S1, adding a titanium source, an aluminum source and an alcohol polymer to anhydrous ethanol, heating and stirring to obtain a mixed solution; S2, adding a mixed solution of anhydrous ethanol and distilled water dropwise into the mixed solution of step S1 for hydrolysis to obtain an initial gel, and the initial gel is dried and calcined to obtain a nano-sheet TiO2-Al2O3 oxide; S3. The nano-sheet TiO2-Al2O3 oxide is impregnated with a vanadium source and a molybdenum source, and then dried and calcined to obtain a V2O5-MoO3 / TiO2-Al2O3 high-temperature denitrification catalyst.
2. The preparation method according to claim 1, characterized in that: In step S1, the alcohol polymer includes any one or more of polypropylene alcohol, polyvinyl alcohol and polybutylene glycol.
3. The preparation method according to claim 1, characterized in that: In step S1, the titanium source includes any one of titanium isopropoxide, tetrabutyl titanate and isopropyl titanate; The aluminum source includes any one of aluminum isopropoxide, aluminum sec-butoxide and aluminum ethoxide.
4. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of the oxides corresponding to the titanium source and the aluminum source is 1:(0.1-0.9); The mass ratio of the oxide corresponding to the titanium source to the alcohol polymer is 1:(0.3-10).
5. The preparation method according to claim 1, characterized in that: In step S1, during heating and stirring, the temperature is controlled to be 30-60° C. and the time is 0.5-2 h.
6. The preparation method according to claim 1, characterized in that: In step S2, during hydrolysis, the temperature is controlled to be 30-60°C and the time is 1-3h; When drying, control the temperature to 80-130℃ and the drying time to 12-48h; During roasting, the temperature is controlled at 450-550°C and the roasting time is 6-12h.
7. The preparation method according to claim 1, characterized in that: In step S3, the vanadium source includes any one or more of ammonium metavanadate, ammonium vanadate and vanadyl oxalate; The molybdenum source includes any one or more of ammonium heptamolybdate, molybdenum nitrate, molybdenum sulfate and molybdenum chloride.
8. The preparation method according to claim 1, characterized in that: In step S3, during drying, the temperature is controlled to be 80-120°C and the time is 1-4h; During calcination, the temperature is controlled at 450-500°C and the calcination time is 4-10h.
9. The preparation method according to claim 1, characterized in that: In step S3, in the high-temperature denitration catalyst, the mass fraction of V2O5 is 0.8%-2.0%, and the mass fraction of MoO3 is 1%-4.5%.
10. A high temperature denitration catalyst, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of ultra-high-temperature denitration catalyst
CN113083286A